Magnetic resonance imaging characteristics of children and adults with paediatric-onset multiple sclerosis - E. Ann Yeh; Bianca Weinstock‐Guttman; Murali Ramanathan; Deepa P. Ramasamy; Laura Willis; Jennifer Cox; Robert Zivadinov (2009)
The purpose of this study was to compare the clinical and quantitative magnetic resonance imaging metrics of paediatric-onset multiple sclerosis to adult-onset multiple sclerosis. It was a prospective comparison of clinical and magnetic resonance imaging characteristics of two paediatric onset multiple sclerosis and two adult onset multiple sclerosis groups that were matched for disease duration. The paediatric-onset-C group consisted of children with paediatric-onset multiple sclerosis with mean disease duration of 2.7 years, whereas the paediatric onset-A group consisted of adults with mean disease duration of 20 years. The adult onset multiple sclerosis-1 and adult onset multiple sclerosis-2 groups were matched to the paediatric onset-C and paediatric onset-A groups. The brain magnetic resonance imaging measures included: T1-, T2- and gadolinium contrast-enhancing volumes and the T2-lesion volume relative magnetization transfer ratio, global and tissue specific white and grey matter brain atrophy and normal appearing grey and white matter magnetization transfer ratio. Regression analyses were employed for magnetic resonance imaging measures. The paediatric onset multiple sclerosis-C (n = 17) and adult onset multiple sclerosis-1 (n = 81) groups had mean disease duration values of 2.7 ± standard deviation 2.0 and 2.6 ± 1.1 years, respectively. The paediatric onset multiple sclerosis-A group (n = 33) and adult onset multiple sclerosis-2 group (n = 300) had mean disease durations of 20 ± standard deviation 10.9 and 20 ± 9.3 years, respectively. In regression analysis, the T2- lesion volume of the paediatric onset multiple sclerosis-C and adult onset multiple sclerosis-1 groups were similar but there was a trend toward higher T1- lesion volume (P = 0.028) in the paediatric onset group. The brain parenchymal fraction and grey matter fraction in the paediatric-onset multiple sclerosis-C group were higher than those for the adult onset multiple sclerosis-1 group (both P < 0.001). The frequency of progressive multiple sclerosis in the paediatric onset multiple sclerosis-A group (27.3%) trended lower (odds ratio = 0.43, P = 0.042) than that in the adult onset multiple sclerosis-2 group (46.3%). The Expanded Disability Status Scale (median; inter-quartile range) in the paediatric onset multiple sclerosis-A group (2.25; 2.5) trended lower (P = 0.058) compared with the adult onset multiple sclerosis-2 group (3.5; 4.0). There was a trend toward lower magnetization transfer ratio values in T2-lesions, normal appearing grey matter and normal appearing white matter and higher grey matter fraction in the paediatric onset multiple sclerosis-A group compared with the adult onset multiple sclerosis-2 group. There was no evidence for differences on T2-lesion volume, T1-lesion volume, brain parenchymal fraction or white matter fraction. Paediatric-onset multiple sclerosis is characterized by a significant disease burden both early and later in the disease course. Despite this, disability is slower to accrue in paediatric onset multiple sclerosis than adult onset multiple sclerosis.